Highly stable rechargeable zinc-ion battery using dimethyl sulfoxide electrolyte. (September 2021) - Kao-ian, W.; Nguyen, M.T.; Yonezawa, T.; Pornprasertsuk, R.; Qin, J.; Siwamogsatham, S.; Kheawhom, S.
Abstract: Due to their high safety, low cost, eco-friendliness, and impressive electrochemical performance, rechargeable zinc-ion batteries (ZIBs) show great potential as electrical energy storage devices for large-scale applications. Nonetheless, recently developed ZIBs still suffer from low cycling stability and high capacity fading. Such shortcomings are caused by the reversibility of both zinc (Zn) and the cathode host material, as well as hydrogen evolution in aqueous electrolytes, which are naturally protic solvents. Herein, dimethyl sulfoxide (DMSO), a polar aprotic solvent, is examined as an electrolyte for a ZIB. Zn stripping/plating in DMSO-based electrolytes shows excellent reversibility and dendrite-free morphology. During charging and resting modes, hydrogen evolution is effectively inhibited. Insertion/extraction of Zn ions in DMSO-based electrolytes into delta-type manganese dioxide (δ-MnO2 ) demonstrates high stability, achieving a decent initial capacity of 159 mAh/g at 50 mA/g and a nominal discharge voltage of 1.15 V. At 100 mA/g charge/discharge cycling, the ZIB, having the DMSO-based electrolyte, can pass 1000 cycles, displaying a capacity retention of 60%. Overall, the improved performance of ZIBs can be attained using DMSO-based electrolytes. Results pave the way towards the practical application of ZIBs. Highlights: Highly stable zinc-ion battery using dimethyl sulfoxide electrolyte. Reversible zinc stripping/plating without passivation and dendrite formation. Stable zinc-ion insertion/extraction into/from manganese oxide structure. No hydrogen production during charging and self-corrosion of zinc in dimethyl sulfoxide electrolyte. Initial capacity of 159 mAh/g with a capacity retention of 60% over 1000 cycles.